2015
DOI: 10.18697/ajfand.72.15395
|View full text |Cite
|
Sign up to set email alerts
|

Impact evaluation of positive deviance hearth in Migori county, Kenya

Abstract: A Positive Deviance (PD) Hearth intervention is a home and neighborhood-based nutrition program for children who are at risk for protein-energy malnutrition in a low resource community. The intervention uses the ‘Positive Deviance’ approach to identify those behaviors practiced by the mothers or caretakers of well-nourished children from poor families and transfers such positive practices to other mothers who are equally disadvantaged economically. Positive Deviance Hearth intervention is designed to treat mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The results show that breastfeeding was initiated within the first hour of the child’s birth in 79.4% of the cases and 89.9% of the controls, and the difference was significant ( p = 0.014) between the two groups. A similar finding from a Positive Deviance/Hearth study in five communities of rural Kenya showed a significant difference in breastfeeding behaviors between mothers of controls and cases ( p ˂ 0.023), with 60.4% of the caregivers/mothers of well-nourished children feeding their infants within an hour compared to 33% of the caregivers of malnourished children [ 14 ]. Commencement of breastfeeding immediately after birth ensures that the newborn receives the “first milk” (colostrum), the baby’s first immunization from diseases that impacts the child’s nutrition status [ 15 ].…”
Section: Discussionmentioning
confidence: 64%
“…The results show that breastfeeding was initiated within the first hour of the child’s birth in 79.4% of the cases and 89.9% of the controls, and the difference was significant ( p = 0.014) between the two groups. A similar finding from a Positive Deviance/Hearth study in five communities of rural Kenya showed a significant difference in breastfeeding behaviors between mothers of controls and cases ( p ˂ 0.023), with 60.4% of the caregivers/mothers of well-nourished children feeding their infants within an hour compared to 33% of the caregivers of malnourished children [ 14 ]. Commencement of breastfeeding immediately after birth ensures that the newborn receives the “first milk” (colostrum), the baby’s first immunization from diseases that impacts the child’s nutrition status [ 15 ].…”
Section: Discussionmentioning
confidence: 64%
“…The positive deviant (hearth nutrition education) approach identifies and transfers good behaviors done by mothers of well-nourished children from disadvantaged households to others in the community with malnourished children [31]. The approach identifies good child feeding, care, and health-seeking behaviors that are available to all community members, even the extremely poor [32].…”
Section: Methodsmentioning
confidence: 99%